Análise do processo de construção de competências em um contexto de inovação tecnológica por demanda emergencial: um estudo de caso sobre o desenvolvimento dos kits diagnósticos para a Covid-19 no CT-vacinas/UFMG - Franciele Garcia da Silva (2023)
Theoretical perspectives on the theme of innovation and competences for innovation have a wide range in organizational studies. However, studies that delve deeper into the subject of competence building as part of innovation development, considering, for example, adverse contexts of emergency demand, still do not have wide dissemination in studies on innovation in organizations. In this research, the vision of innovation is adopted as a complex process that includes the mixture or interaction of diverse and non-linear elements, as well as competence as a practice that takes into account the individual's perception and the events that arise from different contexts. emerging and critical. Given the context of the Covid-19 pandemic, the objective is to analyze, through a case study, the development of a technological innovation in a research institution, through the emergency demand arising from the pandemic context, with a focus on the construction process and sharing skills. For this, the course of the development of diagnostic kits for Covid-19 was analyzed at the Vaccine Technology Center (CT-Vacinas) which is located in Belo Horizonte/MG. Considering the interpretive paradigm and using content analysis, this paper seeks to describe the context of the emergency demand for innovation and analyze its path through the practices identified throughout the process, considering the specificities of the emergency demand imposed by the pandemic. In addition, the specific elements of the competences that characterize and drive the development of innovation were mapped in the case of the development of diagnostic kits for Covid-19 in CT- Vacinas. Through the analyses, categories related to the path of innovation and the development, reconfiguration and sharing of competences through the mapped practices were identified. It is believed that the identified competences can be incorporated into the current CT-Vaccines processes, since they manifested themselves from the practical experience of the body of professionals.